PENGARUH LAMA PENYIMPANAN HIDROLISAT PROTEIN KEPALA UDANG (Litopenaeus vannamei) DENGAN PENAMBAHAN TEPUNG BEKATUL SEBAGAI BAHAN PENGIKAT - Avianto, Terry Previo; Sukoso, Sukoso; Firdaus, Muhammad (Universitas Mataram, 2025)
This study aimed to evaluate the characteristics of shrimp head protein hydrolysate (Litopenaeus vannamei) with the addition of rice bran as a binding agent during specific storage periods. The research utilized proximate analysis, including moisture, protein, fat, ash, and carbohydrate content, analyzed every five days over 15 days. The results showed that moisture and fat content tended to decrease over time, while ash and carbohydrate content increased. Protein content peaked on the 5th day before declining due to protein degradation. The findings suggest that the mixture of rice bran and shrimp head protein hydrolysate has potential as a raw material for protein supplements and carbohydrate-rich foods, depending on the storage duration.